Macro- and microelemental composition of the Antarctic fish blood serum - Voitsitsky, V.; Khyzhnyak, S.; Druzherushenko, O.; Lukashov, D.; Pavlovich, A.; Manilo, O. (Український антарктичний журнал, 2006)
The research materials were selected during the 9-th Ukrainian Antarctic expedition in Academic Vernadsky station region. For analysis the fish samples that related to Nototheniidae, Bathydraconidae and Chaenichthyidae were used. The elemental composition of fish blood serum was estimated by flame atomic absorption spectroscopy and X-ray fluorescence spectroscopy. The elemental analysis of blood serum of the Antarctic fish revealed the species- dependent distribution. The expedience of the fish blood serum use for environmental biotesting is proposed.